Predicting post-hospital lethality in males and females with acute coronary syndrome - R. T. Saygitov; M. G. Glezer; D. P. Sementsov; I. N. Sokolova; N. A. Malygina (Российский кардиологический журнал)
The authors propose prognostic models for separate assessment of post-hospital death risk in males and females, hospitalized with acute coronary syndrome, ACS (possible myocardial infarction or unstable angina). The models are based on parameters registered at admission and further calculation of death risk during one-year post-discharge follow-up period. This predicted risk gives a chance to divide patients into risk groups - with minimal (lethality < 1 %) to maximal (lethality > 30 %) risk, as well as to predict possible time of death. Reproducibility of prognostic results was confirmed for new ACS cases.